On thinning ice: understanding the knowledge, concerns and behaviors towards polar ice loss in Germany. (1st October 2020) - Smith, E. Keith; Eder, Christina; Katsanidou, Alexia
ABSTRACT: Global climate change has the potential to cause rapid changes throughout the world, particularly in the polar regions. While much is known about attitudes towards climate change in general, relatively little is understood about individual orientations towards earth systems affected by climate change, and in particular, polar ice loss. Utilizing novel data from Germany, this study presents a first of its kind analysis of the relationship between knowledge, concern, and individual willingness to make behavioral changes in response to polar ice loss. We find that knowledge of changes to the polar region is positively related to concern for the polar region. But, when looking at willingness to make behavioral changes, concern for the polar regions remains the strongest predictor, while there is little direct effect of individual self-assessed knowledge. Further, concern for the polar region remains a robust predictor of willingness to make behavioral changes, even after individual driving habits are introduced to the model. As such, this analysis builds upon the emerging literature of German orientations towards climate change, as well as understanding the mechanisms by which individuals are willing to engage in behavioral changes in response to changes to the polar regions.